(untitled) (Cadernos de Sociomuseologia, 2022)
The article “Museums for Equality – Diversity and Inclusion: How the assumptions of Cultural Accessibility corroborate the Social Function of Museums” presents and debates current concepts and data about Cultural Accessibility and the rights of people with disabilities to access heritage; introduce a brief historical analysis on the relationship between museum institutions and their public, with enphasis of people with disabilities, and points out some guidelines for the development of museum accessibility programs in order to corroborate with the Social Function of museums. Key words: Cultural Accessibility, People with Disabilities, Inclusion